APPLICATION OF NANOPORE DATA TO THE PIMMS (Pragmatic Insertional Mutation Mapping System) SEQ PIPELINE. - Carlile, Matthew (2023)
Significant developments in next generation sequencing technologies have over the past 15 years allowed novel and exciting opportunities to further our understanding of genomic science. Transposons are mobile regions of DNA that occur frequently throughout the genome, the insertion of these transposable elements play an essential role in both gene regulation and evolution. Locating the positions of transposon insertion into a genome can help our understanding of the role they play in such areas as gene expression and structural variation. Random transposon mediated mutagenesis has proven to be a useful tool in the identification of essential and conditionally essential genes within various bacterial species. Various methods have been generated to identify the regions within a given genome where transposon insertion has occurred. Some of these methods involve complex experimental design in the laboratory, and a high degree of competency in bioinformatics post sequencing.